Historical human remains identification through maternal and paternal genetic signatures in a founder population with extensive genealogical record. Issue 4 (16th February 2020) - Harding, Tommy; Milot, Emmanuel; Moreau, Claudia; Lefebvre, Jean‐Francois; Bournival, Jean‐Sébastien; Vézina, Hélène; Laprise, Catherine; Lalueza‐Fox, Carles; Anglada, Roger; Loewen, Brad; Casals, Ferran; Ribot, Isabelle; et al.
Abstract: Objectives: We describe a method to identify human remains excavated from unmarked graves in historical Québec cemeteries by combining parental‐lineage genetic markers with the whole‐population genealogy of Québec contained in the BALSAC database. Materials and methods: The remains of six men were exhumed from four historical cemeteries in the province of Québec, Canada. DNA was extracted from the remains and genotyped to reveal their mitochondrial and Y‐chromosome haplotypes, which were compared to a collection of haplotypes of genealogically‐anchored modern volunteers. Maternal and paternal genealogies were searched in the BALSAC genealogical record for parental couples matching the mitochondrial and the Y‐chromosome haplotypic signatures, to identify candidate sons from whom the remains could have originated. Results: Analysis of the matching genealogies identified the parents of one man inhumed in the cemetery of the investigated parish during its operating time. The candidate individual died in 1833 at the age of 58, a plausible age at death in light of osteological analysis of the remains. Discussion: This study demonstrates the promising potential of coupling genetic information from living individuals to genealogical data in BALSAC to identify historical human remains. If genetic coverage is increased, the genealogical information in BALSAC could enable the identification of 87% of the men ( n = 178, 435) married in Québec before 1850, with high discriminatory power in most cases since >75% of the parental couples have unique biparental signatures in most regions. Genotyping and identifying Québec's historical human remains are a key to reconstructing the genomes of the founders of Québec and reinhuming archeological remains with a marked grave.